1979
DOI: 10.1042/bj1810737
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the intracellular segregation of polyribosome-associated messenger ribonucleic acid species in the lactating guinea-pig mammary gland

Abstract: 1. Free and membrane-bound polyribosomes were isolated and the associated mRNA species characterized by cell-free protein synthesis, RNA-complexity analysis and polyribosome run-off in vitro. 2. Of the recovered polyribosomal RNA 85% was associated with membrane-bound polyribosomes and contained 87--93% of the total milk-protein mRNA species as assessed by cell-free protein synthesis or RNA-complexity analysis. 3. RNA-complexity analysis showed that the abundant (milk-protein mRNA assumed) species constituted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

1981
1981
1984
1984

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 71 publications
2
45
0
Order By: Relevance
“…Therefore, the existence of casein kinase in the Golgi apparatus (Bingham & Farrell, 1974) seems to corroborate the current view on the biosynthesis of casein and the majority of casein may be synthesized on membrane-bound polysomes, although Devinoy et al (1979) and Houdebine (1977) suggested that free polysomes are responsible for a substantial part of casein synthesis and Craig et al (1979) supported this hypothesis, they suggested that the greater part of this casein may be hydrolysed by intracellular proteases. Regarding the secretion of the casein synthesized on free polysomes, this may occur along the line of fat droplet secretion, since Kurosumi et al (1968) observed electron microscopically that the lumina of lipid droplets contain granules, i. e. casein, when the lumina are removed from the cell membrane.…”
supporting
confidence: 63%
“…Therefore, the existence of casein kinase in the Golgi apparatus (Bingham & Farrell, 1974) seems to corroborate the current view on the biosynthesis of casein and the majority of casein may be synthesized on membrane-bound polysomes, although Devinoy et al (1979) and Houdebine (1977) suggested that free polysomes are responsible for a substantial part of casein synthesis and Craig et al (1979) supported this hypothesis, they suggested that the greater part of this casein may be hydrolysed by intracellular proteases. Regarding the secretion of the casein synthesized on free polysomes, this may occur along the line of fat droplet secretion, since Kurosumi et al (1968) observed electron microscopically that the lumina of lipid droplets contain granules, i. e. casein, when the lumina are removed from the cell membrane.…”
supporting
confidence: 63%
“…Glassware used in the extraction of RNA was heat-sterilized, and all solutions and polyware were autoclaved as described by Craig et al (1979). Limulus haemocyanin was purified as described previously (Lamy et al, 1979), and the native haemocyanin dissociated by pH change and separ-ated into five components or zones by chromatography on DEAE-Sepharose CL-6B (Sullivan et al, 1976).…”
Section: Methodsmentioning
confidence: 99%
“…The RNA was applied to the column equilibrated in 0.5% (w/v) SDS/0.5 M-NaCl/I mM-EDTA/lOmM-Tris/HCl buffer, pH 7.4. After a wash in the same buffer lacking SDS, the column temperature was raised to 600C and the poly(A)+ RNA eluted with lOmM-Tris/HCl buffer, pH 7.4, and precipitated with ethanol and recovered by centrifugation (see Craig et al, 1979).…”
Section: Extraction Ofrnamentioning
confidence: 99%
“…Isolation of poly(A)-containing RNA from free polyribosomal RNA was then performed as previously described in Craig et al (1976). Cell-free protein synthesis and product analysis Cell-free protein synthesis was carried out in a nuclease-treated reticulocyte lysate as described by Pelham & Jackson (1976) and SDS/polyacrylamide-gel electrophoretic analysis of [35S]methionine-labelled peptides was performed by using slab gels as described previously (Craig et al, 1979). Fluorography followed the procedure of Bonner & Laskey (1974), except that dimethyl sulphoxide was replaced by glacial acetic acid throughout (Burckhardt et al, 1979).…”
Section: Buffers and Mediummentioning
confidence: 99%